FINANCIAL CONTROL SYSTEM IN THE MANAGEMENT OF ENTERPRISES - Xalilova Aziza Rustamovna (Journals Park Publishing, 2022)
The presence or absence of effective internal control system at the enterprise has a significant impact on the success of business development, competitiveness increase, development of information system, improvement of quality of accounting and analytical support of enterprise management system. During the research the procedures which are carried out at internal control of financial results are ranked depending on the control stages. Working documents which promote increase of efficiency of planning of inspection, timely collection of proof and full realization of control measures are offered.